Environmental Health Research Involving Human Subjects: Ethical Issues - Resnik, David B. (Libertas Academica, 2008)
This article reviews some of the ethical issues that arise in environmental health research with human subjects, such as minimizing risks to subjects, balancing benefits and risks in research, intentional exposure studies with human subjects, protecting third parties in research, informing subjects about environmental hazards, communicating health information to subjects, and protecting privacy and confidentiality.